Naturalisation of Burundian refugees in Tanzania - Kuch, A (Refugee Studies Centre, University of Oxford, 2016)
Tanzania’s offer of citizenship to some 200,000 refugees received international attention and support. Acknowledging the strengths and flaws of this model could potentially help unlock other situations of protracted displacement around the world.